KONSEP DAN PERENCANAAN SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR - Aljazira Yasyirulgaza Intifada; Merliana Putri Manafe; Sri Marmoah (STKIP Subang, 2026)
Educational supervision is a strategic effort to improve the quality of learning and teacher professionalism. This study aims to analyze the concept and planning of supervision by elementary school principals in improving the quality of education. The method used is a literature review by analyzing various relevant scientific articles, books, and research results. The results show that the principal's supervision includes academic, non-academic, and managerial supervision with principles of being objective, systematic, sustainable, and humanistic. Effective supervision planning includes needs analysis, goal setting, program preparation, instrument determination, and scheduling. The implementation of supervision uses techniques such as classroom observation, interviews, and discussions with clinical, collaborative, and directive approaches. Evaluation and follow-up are crucial stages that include providing constructive feedback and continuous improvement programs. Barriers to supervision include time constraints, principal competence, and teacher resistance. Solutions include training, strengthening communication, and utilizing technology. The conclusion of this study confirms that systematic and sustainable supervision planning by the principal can significantly improve the quality of education in elementary schools.